Polymer-based separators for lithium-ion batteries : production, processing, and properties - DeMeuse, Mark T. (Elsevier, 2021)
Polymer-Based Separators for Lithium-Ion Batteries: Production, Processing, and Properties takes a detailed, systematic approach to the development of polymer separators for lithium-ion batteries, supporting the reader in selecting materials and processes for high-performance polymer separators with enhanced properties. The book begins by introducing the polymeric materials that may be used for separators, as well as characterization techniques, before presenting the available technologies used to produce separators for use in lithium-ion batteries. Each technology is discussed in terms of the advantages and disadvantages of the chosen approach, with the properties of the separators made via each technology also summarized and compared in detail. In addition, areas for further development are addressed, and the limitations of current materials and separators in achieving those goals are highlighted. This is a valuable resource for scientists and engineers in the industry who work on polymer-based battery separators, polymers for electronic/energy applications, and new materials and processes for lithium-ion batteries. In academia, this book will be of interest to researchers and advanced students across the fields of polymer science, materials science, electronics, energy, and chemical engineering.